Particle Swarm Optimization Based Hyper Integral Approach for Enhancing Software Quality - Mantena, Jeevana Sujitha; Subrahmanyam Kodukula (International Journal of Computational and Experimental Science and Engineering, 2025)
Innovation and competitiveness in the software engineering sector have been booming recently. In order to stay in business, software companies need to provide affordable, high-quality software solutions on schedule. A crucial question is whether it is possible to obtain high-quality software products without negatively affecting development effort and cycle time for software developers. Longer cycle times and more development effort are the only ways to deploy software techniques to increase software quality, according to conventional ideas. Another school of thought holds that the understanding aging leader method, which is a Particle Swarm Optimization (PSO) technique, can simultaneously increase software quality, speed up software development cycles, and reduce developers’ effort. A software program defect or bug occurs when a software system fails to meet a functional requirement as stated in the standard specifications or as per the acceptable end-user requirements, even if those requirements are not explicitly mentioned. Integrating quality assurance procedures into every step of the software development lifecycle is the main focus of the Hyper Integral Approach to software quality. By bridging the gap between development and quality assurance, this methodology hopes to boost collaboration, guarantee continuous testing, and raise software quality generally. This research proposes a Hyper Integral Approach (HIA) using Particle Swarm Optimization for enhancing software quality (HIA-PSO-ESQ). The proposed model provides a quality software in less time when contrasted to traditional methods.